Linear discriminant analysis of spatial Gaussian data with estimated anisotropy ratio - Dreižienė, Lina (Lietuvos matematikos rinkinys, 2011)
The paper deals with a problem of classification of Gaussian spatial data into one of two populations specified by different parametric mean models and common geometric anisotropic covariance function. In the case of an unknown mean and covariance parameters the Plug-in Bayes discriminant function based on ML estimators is used. The asymptotic approximation of expected error rate (AER) is derived in the case of unknown mean parameters and single unknown covariance parameter i.e., anisotropy ratio.
Keywords: Bayesian discriminant function; actual risk; expected risk; anisotropy ratio; Gaussian random field